2011
DOI: 10.1007/s10164-011-0285-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of grooming behavior against entomopathogenic fungus Metarhizium anisopliae in the ant Lasius japonicus

Abstract: Social insects employ many types of defense mechanisms against parasites and pathogens because they face high risks from infections due to crowded living conditions with closely related nestmates. Grooming behavior, including self-grooming and allogrooming, can remove fungal spores on the cuticles of social insects and may be a behavioral defense mechanism to improve survivorship. Allogrooming between nestmates has been predicted to be especially important as a defense against ectoparasites. However, little is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 15 publications
5
18
0
2
Order By: Relevance
“…However, self-grooming of the fungus-exposed ants themselves was significantly increased compared with the sham control (r I : t 23 ¼ -3.007, p ¼ 0.006; figure 2a). The latter is in line with other studies generally finding that ants increase self-grooming in response to the exposure of external pathogens like entomopathogenic fungi [24,[46][47][48][49] (but see [50]). Interestingly, elevated self-grooming is not found in termites upon fungal exposure [21,51,52], perhaps owing to less flexibility caused by morphological constraints (absence of a wasp waist) [21].…”
Section: Results and Discussion (A) Grooming Rates (I) Self-groomingsupporting
confidence: 92%
See 1 more Smart Citation
“…However, self-grooming of the fungus-exposed ants themselves was significantly increased compared with the sham control (r I : t 23 ¼ -3.007, p ¼ 0.006; figure 2a). The latter is in line with other studies generally finding that ants increase self-grooming in response to the exposure of external pathogens like entomopathogenic fungi [24,[46][47][48][49] (but see [50]). Interestingly, elevated self-grooming is not found in termites upon fungal exposure [21,51,52], perhaps owing to less flexibility caused by morphological constraints (absence of a wasp waist) [21].…”
Section: Results and Discussion (A) Grooming Rates (I) Self-groomingsupporting
confidence: 92%
“…This prediction may also be valid in other host-pathogen systems with varying ratios of pathogen infectiousness and efficiency of collective host defences, and it can be generalized from our small experimental group sizes to larger, more natural colony sizes. In line with the obtained model predictions, most empirical studies on ants reported increased self-grooming upon pathogen exposure [24,38,40,47,49], while our empirically observed, and theoretically predicted, reduction in allogrooming from the exposed individual to its nest-mates awaits confirmation by other studies.…”
Section: Resultssupporting
confidence: 88%
“…After having undergone this infection protocol, each of the five foragers was kept separately in an individual box (18 × 3 cm) for 1 h and was provided with water and sucrose (0.3 M) ad libitum, before being returned to its mother colony. This 1-h isolation aimed at increasing the success of infection by limiting the removal of fungal spores via allogrooming (Okuno et al 2012;Zhukovskaya et al 2013). As a control group, five additional ants that were sampled from the same colony underwent the same protocol, excepting that no sporulating corpse was put in the Eppendorf.…”
Section: Maintenance Of Ants and Contamination Protocolmentioning
confidence: 99%
“…When parasitoid flies are present, ants have been shown to reduce their foraging behaviour in response (58,85,86) and leaf-cutter ants even have workers who defend foragers from parasitoid attacks (87). For individuals that have picked up fungal spores or infective larval stage helminths, allogrooming and self-grooming can be effective strategies to prevent actual infection (24,60,(88)(89)(90). Other mechanisms of social immunity, such as the spraying of formic acid and use of metapleural gland secretions (91,92) can also kill parasites before infection can commence.…”
Section: Discussionmentioning
confidence: 99%